2009
DOI: 10.1111/j.1365-2702.2007.02241.x
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs and breast self‐examination in a sample of Turkish nursing students and their mothers

Abstract: It is essential that nurses be aware of the factors that contribute to monthly performance of breast self-examination. Cultural factors should be considered in planning educational programmes about breast self-examination practice. Interventions should be designed to enhance nursing students' proficiency in performing breast self-examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…HBM has been used in many health care settings in order to examine many and different health care behaviours and attitudes such as weight management [22], x-ray screening tests [44,45], sexual behaviours [46], coronary heart disease preventive behaviours [47], vaccination behaviours [48,49], diabetes management perceptions [37], nutrition [50], self breast examination perceptions [51-53], prescribed medication compliance [54], and perceptions on the Papanicolaou test [55]. It has also been previously tested and found as an appropriate theoretical model to use for measuring attitudes of nurses and health care workers towards implementing certain aspects of universal precautions from occupational exposure to pathogens [8,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…HBM has been used in many health care settings in order to examine many and different health care behaviours and attitudes such as weight management [22], x-ray screening tests [44,45], sexual behaviours [46], coronary heart disease preventive behaviours [47], vaccination behaviours [48,49], diabetes management perceptions [37], nutrition [50], self breast examination perceptions [51-53], prescribed medication compliance [54], and perceptions on the Papanicolaou test [55]. It has also been previously tested and found as an appropriate theoretical model to use for measuring attitudes of nurses and health care workers towards implementing certain aspects of universal precautions from occupational exposure to pathogens [8,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies assessed the health beliefs about, and the knowledge and practice of BSE among nursing students . The majority of these studies were comparative, focusing on how knowledge of BSE differed between nursing and midwifery students, and how health beliefs differed between nursing students and their mothers, and between nursing students of two countries . These studies reported that nursing students performed BSEs regularly and had sufficient information about them .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies were comparative, focusing on how knowledge of BSE differed between nursing and midwifery students, and how health beliefs differed between nursing students and their mothers, and between nursing students of two countries . These studies reported that nursing students performed BSEs regularly and had sufficient information about them . Kara & Acikel, in a comparative study of health beliefs between nursing students and their mothers, found that nursing students scored higher on health motivation, benefits of BSE and confidence about performing BSE, whereas their mothers scored high on perceived susceptibility to breast cancer and barriers to BSE.…”
Section: Introductionmentioning
confidence: 99%
“…32 In addition, Monthly performance of breast self-examination was more common among women who have recently graduated from high school and university. 35 In this study, the knowledge of students after the intervention had increased and become better. Results of this study was supported by research conducted by Shalini and Malathi, 26 where 72.5% of students had average knowledge about BSE in pretest (before education) and 85% students had good knowledge score in the posttest (after education).…”
mentioning
confidence: 68%
“…34 In addition, there were differences in health belief about BSE and its practice between nursing and their mothers. 35 While other studies show that the female university students have mild knowledge of breast cancer symptoms and management. They did not know about the causes and risk factors of breast cancer.…”
mentioning
confidence: 99%